2021
DOI: 10.1055/a-1389-1203
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Cyclopropanes as Versatile Intermediates for the Diversity-Oriented Synthesis of γ-Lactones, γ-Lactams and δ-Lactams

Abstract: A two-step procedure for the preparation of cyclopropanecarboxaldehyde-1,1-diester from a γ,δ-epoxyester and its synthetic versatility are described herein. The epoxide ring-opening/cyclopropanation process occurs in the presence of Mg(ClO4)2 under heating, resulting in cyclopropanemethanol-1,1-diester in 65% yield. A mild TEMPO-mediated oxidation of this substrate readily generated the corresponding aldehyde in 75% yield, which was applied in the one-pot synthesis of four cyclopropylidene γ-lactams and three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Combined with our studies on derivatization reactions of amides and previous reports, 8 we envisioned that fused-heterocycles 3 may be accessed by treating vinyl cyclopropanecarboxamides 1 with Pd salts to give the important cyclopropa[3,4]pyrrolo[1,2- a ]indolone core 2 of natural products and prodrugs via the aza-Wacker-type oxidation amidation reaction. 9 With this assumption in hand, we attempted all reaction conditions described by previous reports with model reagent 1a, 10 but we found that all efforts failed to give the fused heterocycles 3, indicating that these conditions are not fit for this type of vinyl cyclopropanecarboxamide to undergo the formal [3 + 2] cyclization reaction. Fortunately, the crystal structure of the aza[3.1.0]bicycle 2a, was unambiguously confirmed by X-ray diffraction (CCDC no.…”
Section: Resultsmentioning
confidence: 99%
“…Combined with our studies on derivatization reactions of amides and previous reports, 8 we envisioned that fused-heterocycles 3 may be accessed by treating vinyl cyclopropanecarboxamides 1 with Pd salts to give the important cyclopropa[3,4]pyrrolo[1,2- a ]indolone core 2 of natural products and prodrugs via the aza-Wacker-type oxidation amidation reaction. 9 With this assumption in hand, we attempted all reaction conditions described by previous reports with model reagent 1a, 10 but we found that all efforts failed to give the fused heterocycles 3, indicating that these conditions are not fit for this type of vinyl cyclopropanecarboxamide to undergo the formal [3 + 2] cyclization reaction. Fortunately, the crystal structure of the aza[3.1.0]bicycle 2a, was unambiguously confirmed by X-ray diffraction (CCDC no.…”
Section: Resultsmentioning
confidence: 99%
“…A very few reports are known to synthesize these cyclopropane-amines in moderate to low yields by treating formylcyclopropanes with amines in the presence of NaBH 3 CN, KBH 4 , and Na­(OAc) 3 BH as metal-hydride donors (Scheme ). Surprisingly, three of these known reductive amination reactions are produced cyclopropane-amines in low to moderate yields; may be due to the high reactivity nature of metal-hydrides and formylcyclopropanes. These low-yielding amination reactions are giving inspiration to develop another sustainable method for high-yielding synthesis (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, the same conversion starting from enyne analogues has also been achieved by a photocatalytic pathway [34][35][36] as well as metal-free organocatalytic processes [37][38][39][40][41][42], mechanisms that are similar to the metal carbene processes (Scheme 1a). Another two effective approaches for the synthesis of 3-azabicyclo[3.1.0]hexanes involve the derivatization reactions of substituted cyclopropanes, such as C(sp 3 )-H bond activated alkenylation/amination tandem reactions and intramolecular aminolysis reactions Molecules 2023, 28, 3691 2 of 15 (Scheme 1b) [43][44][45][46][47][48][49][50][51][52][53], and the reaction of functionalized maleimide derivatives with one carbon donor generated in situ derived from substituted diazomethanes, bromo(nitro)methane, substituted α-diazoacetates, and N-tosylhydrazones via an intermolecular [2+1] fusedannulation reaction (Scheme 1c) [54][55][56][57][58][59][60][61][62][63][64]. In particular, the base-induced intramolecular spirocyclization method of the alkylation subunit precursor appeared to be a more efficient proprietary reaction to access 3-azabicyclo[3.1.0]hexane scaffold-containing natural products via aryl metal or radical dearomatization/cyclization reactions (Scheme 1d) [65][66][67][68][69][70][71]…”
Section: Introductionmentioning
confidence: 99%